The skeptical sublime : aesthetic ideology in Pope and the Tory satirists - Noggle, James (Oxford University Press, 2001)
This title examines the role of scepticism in initiating the idea of the sublime in early modern British literature. James Noggle draws on philosophy, intellectual history, and critical theory to illuminate the aesthetic ideology of Pope, Swift, Dryden, and Rochester among other import ant writers of the period. "The Skeptical Sublime" compares the view of sublimity presented by these authors with that of the dominant, liberal tradition of 18th-century criticism to offer a new understanding of how these writers helped construct proto-aesthetic categories that stabilized British culture after years of civil war and revolution, while at the same time their scepticism allowed them to express ambivalence about the emerging social order